2005
DOI: 10.1200/jco.2005.03.127
|View full text |Cite
|
Sign up to set email alerts
|

Autologous and Allogeneic Stem-Cell Transplantation As Salvage Treatment of Acute Promyelocytic Leukemia Initially Treated With All-Trans-Retinoic Acid: A Retrospective Analysis of the European Acute Promyelocytic Leukemia Group

Abstract: These retrospective data suggest that autologous SCT is very effective in APL relapsing after treatment with ATRA if performed in molecular remission. Allogeneic SCT yields few relapses, but it is associated with high TRM when performed after salvage with very intensive chemotherapy. Salvage with arsenic trioxyde, which has lower toxicity, should further improve the outcome of relapsing APL, especially before allogeneic SCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 27 publications
5
117
1
2
Order By: Relevance
“…One out of two cases autografted with a positive PCR assessment relapsed, and only three out of 28 cases (11%) autografted with negative PCR also relapsed. 24 In the patients autografted with negative PCR, relapse-free survival at 7 years increased to 87.3%, indicating that auto-HSCT would be Table 2 Comparison of outocomes from the studies in the autotransplanation for APL effective for the treatment of relapsed APL if performed in molecular CR2; this was consistent with previous reports [25][26][27] (Table 2). Thomas et al 28 reported their experience using ATO as re-induction therapy for 28 relapsed APL patients.…”
Section: Auto-hsct In Cr1supporting
confidence: 86%
See 1 more Smart Citation
“…One out of two cases autografted with a positive PCR assessment relapsed, and only three out of 28 cases (11%) autografted with negative PCR also relapsed. 24 In the patients autografted with negative PCR, relapse-free survival at 7 years increased to 87.3%, indicating that auto-HSCT would be Table 2 Comparison of outocomes from the studies in the autotransplanation for APL effective for the treatment of relapsed APL if performed in molecular CR2; this was consistent with previous reports [25][26][27] (Table 2). Thomas et al 28 reported their experience using ATO as re-induction therapy for 28 relapsed APL patients.…”
Section: Auto-hsct In Cr1supporting
confidence: 86%
“…15 Although no data were available on re-induction and consolidation chemotherapy, or on PCR status of the graft and/or recipients before transplant, the results demonstrated that a large population of patients in CR2 achieved long-term OS after auto-HSCT. De Botton et al 24 also discussed the benefit of auto-HSCT in 50 APL patients who relapsed after ATRA-containing treatment in 2004. The relapse-free survival at 7 years was 79.4% with a TRM of 6% after auto-HSCT.…”
Section: Auto-hsct In Cr1mentioning
confidence: 99%
“…The 7-year RFS (79% vs. 92%) and EFS (61% vs. 52%) rates were not statistically significantly different between patients who received autologous HSCT versus allogeneic HSCT; however, 7-year OS rates were significantly improved with autologous compared with allogeneic HSCT (60% vs. 52%; P = .04). 117 Among patients who received a PCRnegative autograft, the 7-year RFS and OS rates were 87% and 75%, respectively. Although the relapse rates were low with allogeneic HSCT, the reduced OS with this procedure was accounted for by the higher treatment-related mortality observed in the allogeneic HSCT group compared with the autologous HSCT group (39% vs. 6%).…”
Section: Management Of Relapsed Aplmentioning
confidence: 99%
“…Although the relapse rates were low with allogeneic HSCT, the reduced OS with this procedure was accounted for by the higher treatment-related mortality observed in the allogeneic HSCT group compared with the autologous HSCT group (39% vs. 6%). 117 Given the data from this study, the NCCN Guidelines include recommendations for autologous HSCT in patients who achieve second molecular remission, and to reserve allogeneic transplant for those patients who have persistent disease despite salvage therapy.…”
Section: Management Of Relapsed Aplmentioning
confidence: 99%
“…10,11 For APL patients who relapse and subsequently attain a CR2, and for some APL patients who are deemed high-risk for relapse in CR1, autologous hematopoietic SCT (HSCT) continues to have an important therapeutic role. [12][13][14][15] Little is known about the impact of ATO on subsequent autologous HSCT, but two cases of delayed hematopoietic recovery in patients treated with ATO have been reported. 16 To better understand the impact of ATO therapy on hematopoietic recovery, we retrospectively reviewed the histories of all patients who underwent autologous HSCT for APL at our institution since 1994.…”
Section: Introductionmentioning
confidence: 99%